(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Influence of Product Quality, Location, and Service Quality on Coffee Purchasing Decisions at Tahoma Café. Tahoma Cafe experiences monthly revenue fluctuations, with a noted decline indicating a decrease in consumer purchasing decisions. This decline may stem from various factors, such as product quality, location, and service quality. The objective of this study is to examine how product quality, location, and service quality influence coffee purchasing decisions at Tahoma Cafe. The study population includes all consumers who have purchased and consumed coffee at Tahoma Cafe, though their exact number is unknown. A sample of 96 respondents was selected through purposive sampling. Data were gathered via a questionnaire and analyzed using descriptive analysis and SEM-PLS with SmartPLS software version 4.0. The findings reveal that product quality and service quality positively and significantly affect coffee purchasing decisions, while location does not have an impact. Based on these results, the authors recommend that Tahoma Cafe serve sugar separately to allow customers to adjust it to their preference. Additionally, they suggest that all employees enhance their knowledge of the menu and products and undergo training to improve their efficiency in handling customers.